VD_FINDINFO Jug / 2014 / 20 vom 30. Mai 2011 - VD Tribunal cantonal (2011)
FRAIS DE LA PROCÉDURE, DÉPENS, ACQUITTEMENT | 426 al. 1 CPP (CH), 426 al. 2 CPP (CH), 429 al. 1 let. a CPP (CH), 430 CPP (CH), 432 CPP (CH)